Automatic Synthesis of Multimodal Polymers. Issue 4 (7th March 2017) - Leonardi R., Natalie C.; Montgomery, Rick D.; Siqueira, Julia; McAfee, Terry; Drenski, Michael F.; Reed, Wayne F.
Abstract : The current work introduces a feedback based controller for fully automatic production of multimodal polymers in a single reactor. Each mode of the polymer population has its own molecular weight distribution, produced by automatic, successive introductions of chain transfer agent and continuously controlled semibatch feed of monomer into the reactor. Abstract : An automatic molecular weight controller is used in semi‐batch reactions to produce final polymers that contain distinct subpopulations with different molecular weight distributions (MWD). While blending polymers with different MWD is frequently used to make multimodal polymer products, a method is introduced here allowing the multimodal product to be made in successive, automatically controlled stages in the same reactor. The method is demonstrated using free radical polymerization of acrylamide to produce widely separated multimodal MWD. Automatic Continuous Online Monitoring of Polymerization reactions with a Control Interface (ACOMP/CI) was used. Weight average molecular weight ( M w ) in the ACOMP/CI was continuously measured with multi‐angle light scattering and ultra‐violet absorption. The controller used two principles: both polymerization rate and instantaneous molecular weight are proportional to monomer concentration. By controlling monomer flow rate into the reactor, the controller produced a targeted amount of polymer with a desired first M w and then automatically introduced chain transfer agent (CTA) into the reactor to produce a second population of polymers with much lower M w . Subsequently, reactions were performed to produce trimodal populations. This approach is kindred to multi‐stage synthesis of polymers where distinctly different processes are carried out in succeeding stages to produce polymers with highly specific properties.